Islamic Managers and The Role Of Emotional Maturity In Decision-Making (Review of al-Qur’an and Science) - Cahyadi, Iwan Fahri; Fanani, Muhammad Zulham (BISNIS, 2020)
The role of managers in a company has a very strategic position, be it a large, medium or small scale company, although in each company the problems faced have different complexity and risk. This is where managers must be able to analyze problems or problems, choose and sort out various alternatives in solving a problem, take the best decisions and have the lowest risk, and be able to analyze the potential problems that arise in the future. A manager is required not only to have extensive knowledge and insight, but also emotional maturity. Like two sides of a coin, these two things must be utilized simultaneously in decision making so that the right decision is taken. Science and insights are physiological (brain) obtained from schools and their environments. While emotional maturity through religious approaches. Managers who practice religion well (Islamic Managers) then the maturity of their souls is more stable and secure. The manager who is close to God will get the happiness that comes from the endhorpin hormone that is present in humans that has been provided by God.